Semi-analytical study of the rotational motion stability of artificial satellites using quaternions - Santos, Josué Cardoso dos [UNESP]; Zanardi, Maria Cecilia [UNESP]; Matos, Nicholas [UNESP] (Iop Publishing Ltd, 2013)
This study at aims performing the stability analysis of the rotational motion to artificial satellites using quaternions to describe the satellite attitude (orientation on the space). In the system of rotational motion equations, which is composed by four kinematic equations of the quaternions and by the three Euler equations in terms of the rotational spin components. The influence of the gravity gradient and the direct solar radiation pressure torques have been considered. Equilibrium points were obtained through numerical simulations using the softwares Matlab and Octave, which are then analyzed by the Routh-Hurwitz Stability Criterion.